Expanding Opportunities for Rural Finance in Colombia - Gutierrez, Eva (World Bank, Washington, DC, 2016)
The purpose of this note is to provide policy recommendations to improve access to credit of rural populations and small agricultural producers under financially sustainable schemes. Although the agricultural sector remains an important source of employment, agricultural credit is a small fraction of commercial credit in Colombia. The share of agricultural credit in Colombia is below levels observed in other countries in the region. Colombian commercial banks have limited credit volume in rural areas, concentrating their lending activities on more profitable urban populations. General deposit warehouses and the agricultural commodity exchange (Bolsa Mercantil de Colombia (BMC)) provide funding for agricultural activities, but they are underdeveloped compared to regional peers and serve medium and large size producers. Overall use of mobile- and internet-based payment financial products remains low in rural Colombia. According to 2014 Findex survey data, just two percent of adults report using mobile banking, defined as a mobile platform for making transactions from an account at a financial institution. Public credit guarantee system (FAG) coverage should be modified to incentive the use of mobile guarantees and agricultural insurance. This will ensure that financial institutions have only covered tail risks, providing incentives to use mobile guarantees.